Interfacial engineering of CeO2 on NiCoP nanoarrays for efficient electrocatalytic oxygen evolution. (15th February 2021) - Gao, Menghan; Wang, Zhihong; Sun, Shichao; Jiang, Deli; Chen, Min
Abstract: Transition metal phosphides (TMP)-based oxygen evolution reaction (OER) catalysts constructed by interface engineering strategy have a broad prospect due to their low cost and good performance. Herein, a novel CeO2 /NiCoP nanoarray with intimate phosphide (NiCoP)-oxide (CeO2 ) interface was developed via in situ generation on nickel foam (NF). This structure is conducive to increasing active sites and accelerating charge transfer, and may be conducive to regulating electronic structure and adsorption energy. As expected, optimal 1.4-CeO2 /NiCoP/NF delivers a low overpotential of 249 mV at the current density of 10 mA cm −2 with a Tafel slope of 77.2 mV dec −1 . CeO2 /NiCoP/NF boasts one of the best OER catalytic materials among recently reported phosphides (TMP)-based OER catalysts and composite catalysts involving CeO2 . This work provides an effective strategy for the construction of hetero-structure with CeO2 with oxygen vacancies to improve the OER performance of phosphides.